Observational and model studies on transport and inventory of microplastics from a leak accident on the beaches of Yantai. (September 2022) - Zhang, Chen; Wang, Qing; Zhao, Jianmin; Zhao, Yingjie; Shan, Encui
Abstract: We investigated an unexpected microplastic (MP) leakage event that occurred along the coastline of Yantai in January 2021. Sediment samples were collected from three zones on 9 beaches. MPs were identified with an average abundance of 247.6 ± 125.6 items/m 2 on 7 beaches. The total amount of MPs from the leak accident was estimated to be 1.50 × 10 7 items (514.67 kg). The MPs were identified as polyethylene (PE), polypropylene (PP), and PP/PE blends using μ-FT-IR analysis. By utilizing a numerical model, the transmission process and potential source of MPs were demonstrated. The modeling results showed that the MPs might originate from the central and western part of the Bohai Sea and be driven to the beaches of Yantai by northwest wind and wind-induced surface current. However, due to the absence of direct evidence, the simulation results might only indicate the range of the leaking source, which was the movement trajectory of MPs. Highlights: An incident of microplastic leakage in northern China Sea occurred in January 2021. The incident affected >30-kilometer-long coastline with a total input of 514.67 kg. The leaked microplastics originated from polyethylene and polypropylene masterbatches. The microplastics might come from contain the central and western part of Bohai Sea.